DETERMINANTS OF CONSUMPTIVE BEHAVIOR OF SAMARINDA CITY MUSLIM STUDENTS USING SELF-CONTROL AS AN INTERVENING VARIABLE - Sopyana, Sopyana; Tikawati, Tikawati; Wibowo, Arista (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Consumptive behavior is an action that tends to be excessive so that it has an economic impact that can lead to waste and is supported by developments in time, technology and knowledge, one of which is the digital payment system. The use of E-money and Card Payment Tools (APMK) shows a rapid increase so that it has the potential to accelerate economic growth through reducing inflation and the APBN budget. The emphasis on a cashless lifestyle and the concept of balance in consumption are also emphasized, especially in the context of Islamic religious values ​​which teach an understanding of consumption limits and paying attention to problems rather than satisfying desires, this is found in the words of Allah SWT QS. Al-A'raf Verse 31.This research uses quantitative methods. The population in this study were Muslim students from Samarinda City using a convenience sampling technique and determining the sample using the Lemeshow Formula, a sample of 97 respondents was obtained. Data collection was distributed using Google forms and distributing questionnaires to Muslim students in Samarinda City directly. Data analysis techniques use Microsoft Excel 2016 and SPSS 26. The results of this study show that E-money and APMK do not have a significant effect on self-control. Lifestyle has a positive and significant effect on self-control. Self-control has a positive and significant effect on consumer behavior. Self-control does not mediate E-money and APMK on consumer behavior. Self-control partially mediates lifestyle on consumer behavior of Muslim students in the city of Samarinda